The Effect of Etoricoxib on Hepatic Ischemia-Reperfusion Injury in Rats. (5th July 2015) - Kunak, Celalettin Semih; Kukula, Osman; Mutlu, Emre; Genç, Fatma; Güleç Peker, Gülçer; Kuyrukluyıldız, Ufuk; Binici, Orhan; Altuner, Durdu; Alp, Hamit Hakan
Abstract : Ischemia-reperfusion (I/R) damage is known to be a pathological process which continues with the increase of oxidants and expands with the inflammatory response. There is not any study about protective effect of etoricoxib on the liver I/R damage in literature. Objective . This study investigates the effect of etoricoxib on oxidative stress induced by I/R of the rat liver. Material and Methods . Experimental animals were divided into four groups as liver I/R control (LIRC), 50 mg/kg etoricoxib + liver I/R (ETO-50), 100 mg/kg etoricoxib + liver I/R (ETO-100), and healthy group (HG). ETO-50 and ETO-100 groups were administered etoricoxib, while LIRC and HG groups were orally given distilled water by gavage. Hepatic artery was clamped for one hour to provide ischemia, and then reperfusion was provided for 6 hours. Oxidant, antioxidant, and COX-2 gene expressions were studied in the liver tissues. ALT and AST were measured. Results . Etoricoxib in 50 and 100 mg/kg doses changed the levels of oxidant/antioxidant parameters such as MDA, MPO, tGSH, GSHRd, GST, SOD, NO, and 8-OH/Gua in favour of antioxidants. Furthermore, etoricoxib prevented increase of COX-2 gene expression and ALT and AST levels. This important protective effect of etoricoxib on the rat liver I/R can be tested in the clinical setting.